The influence of occupational heat stress on serum inflammatory cytokines among traditional bakery workers in Iran. - Zahra Mirsanei; Yahya Asemani; Milad Derakhshanjazari; Vahid Gharibi; Pirasteh Norouzi; Sepideh Mahdavi; Rosanna Cousins (PLoS ONE)
Heat exposure exceeding the ISO7243:1989 standard limit can contribute to health problems among employees in a variety of workplaces. Ignoring heat standard requirements in hot working conditions such as bakeries results in physiologic and health problems, as well as an elevated risk of later illnesses. In this analytical case-control study, the serum levels of four inflammatory factors (interleukin-1 beta, interleukin-6, tumor necrosis factor-α, and C-reactive protein) were assessed using an enzyme-linked immunosorbent assay. 105 male artisan bakers (in four job classifications in bakeries and staff) were compared based on demographic characteristics and inflammatory factors. The findings of the study showed correlations between serum interleukin-1β, interleukin-6, and C-reactive protein levels and thermal exposure in the occupational environment and employment type. Moreover, some differences in serum level of interleukin-1β and job type were observed. Heat overexposure affected the increase of interleukin-1β and C-reactive protein secretion. As a result of years of working in high-temperature conditions, inflammation can lead to subsequent diseases in workers. To protect their health from this occupational hazard, additional safeguards are needed. Our recommendations could also be applied to overly hot work environments that may cause heat stress in workers.